Pelaksanaan Kegiatan Tutorial di SMA Katolik Tarsisius II Jakarta terkait dengan Strategi Proses Pembelajaran sebelum Memasuki Dunia Perkuliahan - Richard Andrew; Benedict Mario Septian Sondjaja; Jason Huangsadjaja; Anastasya Claudy Jennifer (Lembaga Pengembangan Kinerja Dosen, 2025)
There are plenty of useful activities that can be activated both by high school and higher education entities. One of those activities is the tutorial program to introduce the higher education standard before a high school student picks their preferred program. This program not only set to introduce the differences between higher education and high school standard but also to give plenty of chances. Some of those chances are for higher education students to applied their experiences from the campus and for the alumni to go back into their past high school program. The practiced of this activity run directly in Tarsisius II Catholic’s High School at Jakarta. During the activity, the team that consists of higher education lecturer and students found out that there are significant gaps. One of the most critical gap is to ensure the better two way communication in learning processes. For this kind of thing, the lecturer and teams tried to not only see the paper result. The adaptiveness from what they learn during the tutorial program is also important. As a result, this tutorial work out successfully and could be implemented in several other tutorial program in other high schools.